Synthesis and Supramolecular Structure of {5,5'-Dihydroxy-2,2'-[1,1'-(ethylenedioxydinitrilo)diethylidyne]diphenolato}Cu(II) - Zhao, Li; Cheng, Qian; Zhang, Yu-Jie; Li, Xiang; Liu, Peng-Fei (Asian Journal of Chemistry, 2013)
The title complex {5,5'-dihydroxy-2,2'-[1,1'-(ethylenedioxydinitrilo)diethylidyne]diphenolato}Cu(II) with m.f. C18H20N2O7Cu, has been synthesized and characterized structurally. Cu1 atom is four-coordinated by the four atoms of the donor set (N1, N2, O3 and O5) in the N2O2 coordination sphere and Cu1 approximately lie in a plane. The dihedral angle between the coordination plane of N1-Cu1-O3 and that of N2-Cu1-O5 is 29.1(2)º, indicating that the coordination environment is only slight distortion toward tetrahedral geometry from the square planar structure. Each complex molecule links an adjacent molecule and three crystallizing water molecules into an infinite three-dimensional supramolecular network structure through intermolecular O4-H4···O5, O6-H6···O7, O7-H7C···O3 and O7-H7D···O1 hydrogen-bonding interactions.